Understanding the modern sociology of blood donation, a retrospective study of voluntary blood donors belonging to district Attock Punjab, Pakistan - Naeem Bukhari; , Nadeem Sharif; Aaqib Ali; Abdul Majid; Wali Ur Rehman; Inam-u-llah (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: There is a huge difference in blood donation and blood transfusion demand in developing countries like Pakistan. However, the annual blood transfusion demand in Pakistan has increased up to 1.5 million bags and the blood donation ratio is still less than one percent. Our study aims to assess the sociodemographic barriers related to blood donation in District Attock Punjab, Pakistan. METHODOLOGY: A retrospective study following a convenient sampling method was designed at the Centre for Human Genetics, Hazara University Mansehra, and conducted at District Head Quarter Hospital (DHQ) Attock, Punjab Pakistan. Sociodemographic data of the blood donors were recorded on pre-designed questionnaires and laboratory outcomes were noted after donor screening and blood group testing as well. The standard protocols for donor screening and blood group testing were ensured by the kit method. RESULTS: According to 680 voluntary blood donors from five adjacent areas of Attock, Punjab, Pakistan, Among healthy blood donors 547(91%) of blood donors have either type of Rh +Ve blood group and only54( 9%) have Rh -Ve blood group. A huge difference in gender-specific blood donors was recorded. The female blood donor ratio was recorded at only 1%, whereas 99% of blood donations were recorded from male donors. The mean age of donors was calculated as 28 ± 0.3 years. The highest number of blood donors 415(61%) were laborers p≤0.001 . CONCLUSION: Sociodemographic factors, like the behavior of the blood donors, educational level, professional status, and awareness of blood donation criteria, greatly influence blood donations.